Tenecteplase in Pulmonary Embolism Patients: A Meta-Analysis and Systematic Review - Zhang, Zhu; Xi, Linfeng; Zhang, Shuai; Zhang, Yunxia; Fan, Guohui; Tao, Xincao; Gao, Qian; Xie, Wanmu; Yang, Peiran; Zhai, Zhenguo; Wang, Chen (Frontiers in Medicine, 2022)
Objective To assess the efficacy and safety of tenecteplase in patients with pulmonary embolism (PE). Methods We completed the literature search on May 31, 2021 using PubMed, EMBASE and the Web of Science. Analyses were conducted according to PE risk stratification, study design and duration of follow-up. The pooled risk ratios (RRs) and its 95% confident intervals (CIs) for death and major bleeding were calculated using a random-effect model. Results A total of six studies, with four randomized controlled trials (RCTs) and two cohort studies, were included in this study out of the 160 studies retrieved. For patients with high-risk PE, tenecteplase increased 30-day survival rate (16% vs 6%; P = 0.005) and did not increase the incidence of bleeding (6% vs 5%; P = 0.73). For patients with intermediate-risk PE, four RCTs suggested that tenecteplase reduced right ventricular insufficiency at 24h early in the onset and the incidence of hemodynamic failure without affecting mortality in a short/long-term [<30 days RR = 0.83, 95% CI (0.47, 1.46);≥30 days RR = 1.04, 95% CI (0.88, 1.22)]. However, tenecteplase was associated with high bleeding risk [<30 days RR = 1.79, 95% CI (1.61, 2.00); ≥30 days RR = 1.28, 95% CI (0.62, 2.64)]. Conclusions Tenecteplase may represent a promising candidate for patients with high risk PE. However, tenecteplase is not recommended for patients with intermediate-risk PE because of high bleeding risk. More large-scale studies focused on tenecteplase are still needed for PE patients.